CASH SALES SYSTEM ON CV. NOTICES MANGGUNAKAN CREATIVE FURNITURE WITH VISUAL BASIC 6.0, MICROSOFT ACCESS 2003, AND CRYSTAL REPORT 5.8 - Rachmad Radytiawan; Diyah Ruri Irawati, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Creative CV.Cipta Furniture is a store that sells various items of furniture, becausethe process is performed manually in its workmanship is assessed to be ineffectiveand inefficient because of frequent errors caused by human error is neededcomputerization to increase the effectiveness and efficiency in company runningspeed. To simplify the work required in terms of sales programs and computerapplications programming language Microsoft Visual Basic 6.0, developed from theBasic Language. Microsoft Visual Basic 6.0 Programming Language which is basedVisual Programming and easy to use in making an application. Microsoft Access2003 as a medium to create the database because of the ease is given, and CrystalReport 8.5 as a medium to make a report.Based on that analysis, the authors make, these business entities in administrativeprocesses in the sales department is still done manually such as creating invoices andcreate reports that support the running of the company.In this case there are multiple ways to solve these problems, including flow of theproposed document, context diagram, diagram of zero, Entity Relationship Diagram,Input Output normalization and design programs that will be created with the supportsoftware Microsoft Visual Basic 6.0